Correlation between Pivot Shift Test and Arthroscopic Diagnosis of Anterior Cruciate Ligament Tear in Chronic Knee Injury - Majed Aswad Alsaad; Omar Farooq Radeef; Mohammad Jassam (Academic Journal of Clinicians, 2025)
Background: Anterior cruciate ligament tear is a common problem among knee joint injury. It is important to be familiar with the diagnosis of this injury properly in order to be dealt with appropriately. There are many clinical test that aid in the diagnosis of this injury which include anterior drawer, lichtman and pivot shift tests. Objective: Correlation between pivot shift test and arthroscopic finding in diagnosis of anterior cruciate ligament tear . Patients and Methods: Prospective cohort randomized study obtained from December 2017 till December 2018 at Baghdad medical city complex (Ghazi AL Hariri teaching hospital plus Private Nursing Home hospital), for (54) young male and (10) female patients sustaining chronic knee joint injury who underwent knee joint arthroscopy. All patients were examined under anaesthesia with pivot shift test firstly, then arthroscopic exam were done to the patients. Results: A total of 64 patients had been undergone arthroscopy during the study period which last for one year that met the inclusion criteria. Their ages range from 19-38 year with the mean age was (27.7 ± 4.8) year. 44 of sixty four were found to have positive pivot shift test (68.75%), 20 of them were negative result test 31.25%. 47 patients of sixty four were found to have ACL tear proved by arthroscopy, 42 patients among them had positive pivot shift test and the rest (only five patients) had negative pivot shift test, thus 89.36% of pivot shift test positive patients had ACL tear proved by arthroscopy. Seventeen patients of sixty four were found to have intact ACL proved by arthroscopy, fifteen patients among them had negative pivot shift test and the rest (only two patients) had positive pivot shift test. Conclusion: Pivot shift test is specific for diagnosis of anterior cruciate ligament tear